Why 'state of the art' monetary theory was unable to anticipate the global financial crisis: a child's guide - Colin Rogers (European Journal of Economics and Economic Policies: Intervention (EJEEP), 2014)
State of the art' monetary theory was unable to anticipate or understand the global financial crisis because it rested on microeconomic foundations that precluded any meaningful role for money, finance or banking. These analytical and conceptual flaws have been known for a long time. But many either ignored or misunderstood their implications. This note provides a largely non-technical explanation of the conceptual flaws in 'state of the art' monetary theory that rendered it unable to anticipate, or understand, the global financial crisis of 2007–2008; and rendered it thereafter effectively useless as a guide to what should be done.
Keywords: E40; E42; E50; D53; 330; time-0 auction; money-less Walrasian-Arrow-Debreu models